2011
DOI: 10.1038/oby.2011.165
|View full text |Cite
|
Sign up to set email alerts
|

B Cell‐Activating Factor Controls the Production of Adipokines and Induces Insulin Resistance

Abstract: Visceral adipose tissue (VAT) inflammation has been linked to the pathogenesis of insulin resistance and metabolic syndrome. VAT has recently been established as a new component of the immune system and is involved in the production of various adipokines and cytokines. These molecules contribute to inducing and accelerating systemic insulin resistance. In this report, we investigated the role of B cell‐activating factor (BAFF) in the induction of insulin resistance. We investigated BAFF levels in the sera and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
70
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 24 publications
3
70
0
Order By: Relevance
“…11VATs in high-fat diet (HFD)-fed mice. 13 We also found that in these mice, BAFF-R was preferentially expressed in the VATs and liver, 13 in addition to B cells and plasma cells. Furthermore, we found that NASH patients have higher serum BAFF levels than simple steatosis patients.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…11VATs in high-fat diet (HFD)-fed mice. 13 We also found that in these mice, BAFF-R was preferentially expressed in the VATs and liver, 13 in addition to B cells and plasma cells. Furthermore, we found that NASH patients have higher serum BAFF levels than simple steatosis patients.…”
mentioning
confidence: 71%
“…The HFD group was fed an HFD (60% fat, 20% protein, and 20% carbohydrates; 520 kcal/100 g; D12492; Research Diets, New Brunswick, NJ, USA), as described previously. 13 All animals received humane care, and the study protocols complied with the guidelines of Ehime University.…”
Section: Materials and Methods Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…WAT has a role in the regulation of whole-body energy metabolism and its endocrine function has a critical role in the development of obesity and its metabolic and cardiovascular complications by secreting cytokines/adipokines in distorted proportions. In obese individuals, monocyte and B and T lymphocyte infiltration into the adipose tissue results in low-grade inflammatory state associated with a rise in circulating C-reactive protein (CRP) which could be used as a marker for the development of type 2 diabetes mellitus (T2DM) and insulin resistance (IR) [2][3][4]. However, it should be noted that obesity itself will not lead to the development of IR but, the adipose tissue inflammatory condition is the culprit in metabolic disorders of humans [2].…”
mentioning
confidence: 99%
“…In obese individuals, monocyte and B and T lymphocyte infiltration into the adipose tissue results in low-grade inflammatory state associated with a rise in circulating C-reactive protein (CRP) which could be used as a marker for the development of type 2 diabetes mellitus (T2DM) and insulin resistance (IR) [2][3][4]. However, it should be noted that obesity itself will not lead to the development of IR but, the adipose tissue inflammatory condition is the culprit in metabolic disorders of humans [2]. This fact is further supported by a study on metabolically normal obese postmenopausal women who had exhibited lower CRP and alpha-1 antitrypsin levels suggesting a protective role of these inflammatory markers against cardiometabolic risks [5].…”
mentioning
confidence: 99%